Effectiveness of a handmade shell-based substrate for the breeding of Biomphalaria glabrata under laboratory conditions - Rodrigues, João Gustavo Mendes; Lira, Maria Gabriela Sampaio; Nogueira, Ranielly Araújo; Gomes, Gleycka Cristine Carvalho; Licá, Irlla Correia Lima; Viegas-Melo, Davi; Teles-Reis, Andrea; Miranda, Guilherme Silva; Silva-Souza, Nêuton (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
Efficient snail production is essential for the proper maintenance of the Schistosoma mansoni life cycle in the laboratory. In order to improve the breeding of Biomphalaria glabrata under laboratory conditions, this study aimed to demonstrate the effectiveness of a handmade shellbased substrate on the physiological performance of B. glabrata. The shells used to make the substrate were cleaned, sterilized and macerated until a powder was obtained (yield of 92.3%). B. glabrata specimens were randomly assigned to three treatment groups: negative control group (NCG) exposed to a clay-only substrate; a positive control group (PCG) containing clay, oyster flour and calcium carbonate; and the test group (TG) with the shell-based substrate and clay. B. glabrata bred in the test group showed improved growth, sexual maturity, fertility, mortality rate, and shell morphology when compared to the NCG, and similar to the PCG. Therefore, the shell-based substrate proved to be efficient and has a low cost for the breeding of B. glabrata.